EFEKTIVITAS KONSELING KELOMPOK DALAM MENGATASI KENAKALAN REMAJA - Cadra Prasiska Rahmat, Dzifa Hesti Hazal Wardhani, Elis Nur Mutia, Fairah Dwi Agustin Nugraha, Salsa (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2024)
Adolescence is defined as a transition period, from childhood to adulthood between the ages of 12 and 18 years. This period is also a period for an individual who will experience changes in various aspects, such as cognitive (knowledge), emotional (feelings), social (social interaction) and moral (morals). This study aims to determine the effectiveness of group counseling in overcoming juvenile delinquency. The method used in this study is a literature study. The results of this study are that various literatures analyzed show similar findings that group counseling is effective in overcoming juvenile delinquency.